Political Connections, Governance Mechanisms, Firm Size, and Sustainability Report Disclosure in Indonesian Mining Companies 2021–2024 - Rania Fairuz Khalisha; Wiwik Saraswati; Yanzil Azizil Yudaruddin (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to examine the effect of political connection, governance mechanism, and firm size on sustainability report disclosure of mining companies listed on the Indonesia Stock Exchange. The study is motivated by the still limited transparency of a number of mining companies in disclosing the social and environmental impacts of their operational activities, as well as the inconsistency of previous research findings regarding the determinants of sustainability report. This study employed a quantitative approach using secondary data obtained from the annual reports of mining companies during the 2021–2024 period. The sample was determined using purposive sampling, resulting in 143 firm-year samples that met the criteria. The data were analyzed using multiple linear regression analysis with the assistance of SPSS. The results indicate that political connection and governance mechanism have no effect on sustainability report disclosure, whereas firm size has a positive effect on sustainability report disclosure. These findings suggest that mining companies' decisions to disclose sustainability reports are driven more by operational scale and public legitimacy pressure than by political proximity or formal governance quality. This study contributes empirically to the development of legitimacy theory and provides considerations for regulators and mining companies in encouraging transparency in sustainability reporting.